Citizenship in the Algerian Higher Education - BOUHENIKA, Meriem (Journal of Human Sciences, 2024)
The prominent role of universities always targets teaching academic/scientific skills. Consequently, students get equipped with professional training for jobs. Modern universities, however, are required to provide more serious trainings/engagement to form not only intellectuals but also effective citizens. Similarly, the Algerian university struggles providing quality teaching, whereas, graduates feel lost and behave inappropriately. This paper insists on the role of university in building good citizens and integrating citizenship education. Does university guarantee effective citizenship? Should students learn to be good citizens? Does university serve the public through teaching? It is assumed that universities must train students to be ready for challenges and act appropriately. A questionnaire is distributed to teachers on the contribution of university to form effective citizens. Results report that teachers favour involving the university to train students to be democratic, creative, constructive citizens. They also conclude that quality teaching prepares students to contribute to the public good.